2011
DOI: 10.1001/archgenpsychiatry.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates in Patients With Anorexia Nervosa and Other Eating Disorders

Abstract: Individuals with eating disorders have significantly elevated mortality rates, with the highest rates occurring in those with AN. The mortality rates for BN and EDNOS are similar. The study found age at assessment to be a significant predictor of mortality for patients with AN. Further research is needed to identify predictors of mortality in patients with BN and EDNOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
1,455
5
45

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,196 publications
(1,636 citation statements)
references
References 56 publications
34
1,455
5
45
Order By: Relevance
“…It has been documented in many studies that chronically ill, low-weight AN patients such as the one in our study do have a much increased mortality risk. 72 The causes of death typically are related directly to consequences or complications of the illness (via malnutrition or abnormal weight control methods), and this is thought to be the case here. Previous trials of AN outpatient treatment in adults have reported deaths.…”
Section: Harmsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been documented in many studies that chronically ill, low-weight AN patients such as the one in our study do have a much increased mortality risk. 72 The causes of death typically are related directly to consequences or complications of the illness (via malnutrition or abnormal weight control methods), and this is thought to be the case here. Previous trials of AN outpatient treatment in adults have reported deaths.…”
Section: Harmsmentioning
confidence: 99%
“…[72][73][74][75][76][77] Universal prevention programmes are a useful element of the prevention portfolio as they allow us to tackle elements of the social environment that are known to be risk factors for EDs, such as perceived pressure from peers towards thinness. 78,79 Universal interventions also do not face some of the difficulties of selective programmes, namely the stigma associated with participating and the low uptake of those identified as being at risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last years, the incidence of anorexia increased significantly in this high-risk group, although the overall incidence rate remained stable [3,4,5]. Anorexia is a very serious and even life-threatening psychiatric illness with a mortality rate of 5 to 6%, higher than all other mental disorders [6,7,8].…”
Section: Introductionmentioning
confidence: 97%
“…Anorexia nervosa is a disease of a persistent character and a diversified course; it is also fraught with a high risk of death. It has been estimated that mortality indices among anorectic patients are at least 5 times higher than expected [2,3,8,9].…”
mentioning
confidence: 95%